Immunohistochemical expression of hormone receptors, Ki-67, endoglin (CD105), claudins 3 and 4, MMP-2 and-9 in endometrial polyps and endometrial cancer type I - Peres, Gustavo Filipov [UNESP]; Spadoto-Dias, Daniel [UNESP]; Bueloni-Dias, Flavia Neves [UNESP]; Leite, Nilton Jose [UNESP]; Elias, Leonardo Vieira [UNESP]; Custodio Domingues, Maria Aparecida [UNESP]; Padovani, Carlos Roberto [UNESP]; Dias, Rogerio [UNESP] (Dove Medical Press Ltd, 2018)
Objective: The aim of this study was to investigate the malignant potential of endometrial polyps (EP) by assessing the immunoexpressions of both estrogen receptor (ER) and progesterone receptor (PR), Ki-67 cell proliferation index, neovascularization network (endoglin - CD105), cellular adhesion molecules (claudins 3 and 4), and extracellular matrix proteins (MMP-2 and -9) in both EP and endometrioid adenocarcinoma (type I) in comparison with the normal endometrium. Study design: This is a cross-sectional comparative study. Patients were identified from the database of Botucatu Medical School, Sao Paulo State University (BMS-UNESP) Clinical Pathology Laboratory. Setting: The study was conducted using a convenience sample of patients attending the Sectors of Gynecologic Endoscopy and Family Planning and Gynecologic Oncology of the Department of Gynecology and Obstetrics of BMS-UN ESP, Brazil. Patients: A total of 90 women were allocated into the following three groups: EP without atypic (EP, n=30), endometrioid endometrial cancer (EC, n=30), and normal endometrium (control, n=30). Methods: Epidemiological and clinical data were obtained by reviewing medical records. Adenocarcinoma and control cases were assessed using the tissue microarray technique. The immunoexpressions of ER, PR, Ki-67, CD105, claudins 3 and 4, and MMP-2 and -9 were assessed in paraffin blocks containing sections of the largest polyploid lesion fragment and tissue microarray recipient blocks. Major results: Compared to the control group, significant differences in the expression of ER (P<0.001), PR (P<0.05), Ki-67 (P<0.001), C D105 (P<0.001), and claudin 3 (P <0.001) were observed in EP and EC. No significant differences were found between EP and EC (P >= 0.05). M M P-2 and -9 expression were nearly absent in all groups. Conclusion: The malignant potential of EP could not be determined through the immunohistochemical parameters used in this study. No MMP-2 or -9 expression was observed in any endometrial tissue sample. Further studies are necessary for a better understanding of the biomolecular mechanisms underlying endometrial carcinogenesis.
Keywords: endometrium/pathology; immunohistochemistry; endometrial neoplasia; polyps/epidemiology